The perceptions of selected Filipino interior designer on sustainable design and the coherence of these perceptions in their actual practice of the interior design profession - Deray, Stephanie Diane M. (UP College of Home Economics, 2012)
The study aimed to identify the definitions understood by selected Filipino interior designers of sustainable design and to find out if there is a consistency between their definitions and their actual applications of sustainable design. The study also sought to establish if there is a gap between selected interior designers' perception of sustainable design and their actual practice. Using purposive sampling, the respondents were 22 Filipino interior designers who are members of the Philippine Institute of Interior Designers. They were selected from a dtabase posted by a PIID member on-line. The data was gathered by sending out an online survey form created using Google Documents which automatically tabulated the results of the survey. The results of the survey were tabulated and evaluated in terms of whether the respondents were able to identify sustainable design from green design and ecological design. Likewise, it was determined whether the respondents apply sustainable design in their actual practice of the profession. The results show that there were no distinct topics for discussion on the differences in the profile of respondents. However, data confirmed that there is confusion in the respondents' understanding of sustainable design. Furthermore, there are also inconsistencies between the respondents' definition of sustainable design and their actual application of this concept to their practice of the profession. The study estblished that clarification on sustainable design theory is needed among interior designers to avoid confusion, and that this confusion could be prevented by including sustainable design in the theories class of interior design undergraduate students.